Dependência de trajetória no setor elétrico - Müller, Matheus (2013)
The proccess of reform of the electricity industry in Brazil followed the global trend over the years 1990 and materialized in line with market principles. The purpose of social, economic and political state went through a long process of restructuring where new regulatory framework was established for the electricity sector. The logic state back to make room for the competitive logic, a kind of return to the origins of the development of the electrical industry, albeit with a conformation organizational and productive much more dense and complex. It is on this background that focuses the study, with the main objective to analyze national policy of restructuring the electricity sector over the decade from 1990 to 2000, from the approach of path dependence. This analytical method is relevant to show that even the innovative initiatives in terms of public policies carry with them elements of structures, institutions and previous policies that act to reinforce actions already initiated. The results point to a policy of power sector reform marked by continue even after the exhaustion of their models.